2021
DOI: 10.1016/j.heliyon.2021.e07370
|View full text |Cite
|
Sign up to set email alerts
|

Novel greenly synthesized titanium dioxide nanoparticles compared to liposomes in drug delivery: in vivo investigation on Ehrlich solid tumor model

Abstract: Aims In a previous work, a pure crystalline titanium dioxide nanoparticles (TiO 2 NPs) were synthesized by green synthesis technique using Aloe vera leaves extract as reducing agent. In this work, we are aiming to investigate the potential of the novel greenly synthesized TiO 2 NPs as a nano-drug delivery system for the anticancer drug, doxorubicin (Dox). Main methods The cytotoxicity of the synthesized TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The encapsulation of T1, T2 and T3 was realised by following the procedure mentioned elsewhere 19 with minor modifications. Three sets of drug-NPs solutions were prepared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The encapsulation of T1, T2 and T3 was realised by following the procedure mentioned elsewhere 19 with minor modifications. Three sets of drug-NPs solutions were prepared.…”
Section: Methodsmentioning
confidence: 99%
“… 18 The smaller the NPs, the more penetrating power they possess. Fadeel et al 19 synthesised anatase TiO 2 NPs having sizes in the range 13–18 nm using aloe vera leaf extract. They were loaded with doxorubicin (DOX) exhibiting high encapsulation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…1 a. The pattern observed in the lower region of 2θ from 10 to 27° indicates the characteristic peak of chitosan 50 , 51 . The XRD peaks observed at 27.214, 35.855, 38.987, 41.019, 43.845, 54.1, 56.425, 62.495, 63.824, 68.771, 69.558, 72.267 and 76.454° correspond to (110), (101), (200), (111), (210), (211), (220), (002), (310), (301), (112), (311) and (202) planes respectively.…”
Section: Resultsmentioning
confidence: 89%
“…The bands observed at 3260 ± 4 cm −1 in all the studied samples were assigned to the stretching vibration of -OH groups of SA 46 . The IR band at 1325.5 ± 1.5 cm −1 was ascribed to the stretching vibration of Ti–O–Ti of TiO 2 NPs 47 and also to C–O asymmetrical stretching of SA 48 . Changes in the fingerprint regions of the IR spectrum, as well as in the shape and intensity of bands at a range of 1597–1645 cm −1 , at 1028 ± 4 cm −1 , at 1085 ± 2 cm −1 , at 1325.5 ± 1.5 cm −1 , and at a range of 1412–1420 cm −1 , were observable.…”
Section: Resultsmentioning
confidence: 99%
“…Still, they were safe to standard human embryonic kidney cell lines up to 100 μg/ml. Abdel Fadeel et al 47 reported that, at concentrations from 0.01 to 100 μg/ml, the greenly synthesized TiO 2 NPs were nontoxic to breast adenocarcinoma cell and normal human skin fibroblast. Based on the positive results of the biocompatibility test, it can be concluded that PVA:SA:TiO 2 nanocomposite films studied here had tremendous potential for use as wound dressing materials.…”
Section: Resultsmentioning
confidence: 99%